Analisis QirÃ¢â€™at Sabâ€˜ah pada Kitab TafsÃ®r al-MunÃ®r Karya Wahbah al-Zuhaili. - Ismail Pane (Program Pascasarjana Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
The analysis of Sabâ€˜ah QirÃ¢â€™at of the Tafsir of al-MunÃ®r by Wahbah al-ZuhailÃ® Along with the development of Islam, QirÃ¢â€™at also spreads to several nations and widely learned by Muslims. It creates many versions of reading of which some of them are well validated, which were coming from the Prophet, but some are still in doubt, which is possibly not from the prophet. The main matter of this articel is to describing how Wahbah al-ZuhailÃ® uses different QirÃ¢â€™at in TafsÃ®r al-MunÃ®r of al-Baqarah verses and how is the influence of different QirÃ¢â€™at toward the interpretation of al-Qurâ€™Ã¢n al-Baqarah verses based on Wahbah al-ZuhailÃ®. This research is a Library Research which emphasizes on the literature by analyzing the content of the literature which is related to the primary and secondary sources. The primary data were presented by TafsÃ®r al-MunÃ®r. While the secondary data were the references which are not related directly to the topic. The conclusion of this research is Wahbah al-ZuhailÃ® uses QirÃ¢â€™at differences as the instrument of its interpretation, even in al-Baqarah that has 286 verses which have 184 words/sentences found in 123 verses, he used the QirÃ¢â€™at of the Seven Imams. And Wahbah al-ZuhailÃ® interpreted the verses which have different QirÃ¢â€™at indicated that there is an effect of al-Qurâ€™an interpretation. However, not all QirÃ¢â€™at differences in al-Qurâ€™Ã¢n have effects on the interpretation especially al-Baqarah verses. It can be proven on the interpretation of article 222 of al-Baqarah verse. However, Wahbah al-ZuhailÃ® stated that the QirÃ¢â€™at differences in al-Baqarah verse have effects on the interpretation on only article 222, meanwhile, the article 37 and 259 and the others do not have effects on the interpretation and have different meanings, but the purposes are the same.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersianÂ // Â TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//